England in a Miniature in Mike Leigh's "The Short and Curlies" - Śliwińska, Anna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
Mike Leigh’s films are known for having kept the same tone and having played out the same melody for years. It is noteworthy that all the themes which Mike Leigh developed in his subsequent films, appeared in The Short and Curlies. Short scenes from the life of the English in The Short and Curlies can be seen in each scene of the film. From details such as a street with a perfectly straight terrace of houses with small gardens to social questions that are constant in the British culture. This ordinary, everyday observation gave rise to the plot of The Short and Curlies, revolving around a love affair of Joy (Sylvestra Le Touzel), a young woman working at a chemist’s and Clive (David Thewlis), a man who communicates with her only by means of his humourless jokes. Another story in the film is a complicated relationship of an eccentric hairdresser Betty (Alison Steadman), who is more interested in the life of the pharmacist than in the life of her own daughter Charlene (Wendy Nottingham). As Ewa Mazierska says: “Mike Leigh was once called the painter of miniatures – his films and TV productions for which he is equally praised and admired, concentrate on life of «small people with small gardens»”. Mike Leigh knows that his strengths are well written dialogues and this extraordinary skill to become a fictional character possessed by the actors he chooses.

Filmy Mike’a Leigh od lat utrzymują ten sam ton i wygrywają podobną melodię. Warto zauważyć, że wszystkie wątki, do których odwoływał się reżyser w późniejszych filmach, pojawiły się już w Krótkie i kręcone. Minatury związane z życiem Anglików pojawiają się w każdym ujęciu tego filmu. Od drobnych szczegółów dotyczących pokazywania kolejnych ulic z równymi domami i ogródkami, aż po, stałe w kulturze brytyjskiej, pytania społeczne. Z tej zwykłej, codziennej obserwacji powstała też fabuła Krótkie i kręcone, która krąży wokół romansu między Joy (Sylvestra Le Touzel), młodą kobietą, pracującą w aptece, a Clivem (David Thewlis) mężczyzną, który komunikuje się z nią tylko poprzez pozbawione humoru dowcipy. Drugim wątkiem ukazanym w filmie jest skomplikowana relacja ekscentrycznej fryzjerki Betty (Alison Steadman), którą życie młodej aptekarki interesuje bardziej niż los jej córki Charlene (Wendy Nottingham). Jak pisze Ewa Mazierska: „Kiedyś nazwano Mike’a Leigh malarzem miniatur – jego filmy, a także produkcje telewizyjne, za które jest w Brytanii równie ceniony i szanowany, koncentrują się na życiu <<małych ludzi z małymi ogródkami>>”1. Mike Leigh wie, że jego atutami są świetnie napisane dialogi i wprost niebywała umiejętność wchodzenia w postać, która charakteryzuje pracę wybranych przez niego aktorów. 1. E. Mazierska, Z czułością, „Kino” 1997, nr 3, s. 37.
Anglia w miniaturach w filmie Mike'a Leigh'a „Krótkie i kręcone”
Anna Śliwińska Katedra Filmu, Telewizji i Nowych Mediów UAM, England in a Miniature in Mike Leigh's “The Short and Curlies”, Anglia w miniaturach w filmie Mike'a Leigh'a „Krótkie i kręcone” „Images” 2012, vol. X: Microcosmos, red. A. Szpulak i W. Otto, nr 19, s. 23-31, ISSN 1731-45x, język: angielski
Keywords: Mike Leigh; The Short and Curlies; England; British culture; Krótkie i kręcone; Anglia; kultura brytyjska